An overview of the chemical constituents, pharmacological properties, and safety evaluation of Camellia sinensis flowers - Eric Wei Chiang Chan (Journal of Applied Pharmaceutical Science, 2024)
The young leaves of Camellia sinensis (L.) Kuntze is most studied in vitro and in vivo with little attention on other parts of the plant. This overview is focused on the chemical constituents and pharmacological properties of the lesser-known flowers of C. sinensis with brief descriptions of their morphology, reproductive biology, and uses. Studies on the chemical constituents and pharmacological properties of C. sinensis flowers are on flower buds and not on open flowers. Chemical compounds found in tea flowers include flavonols, catechins, polysaccharides, saponins, proteins, alkaloids, spermidine derivatives, and anthocyanins. Major pharmacological properties of C. sinensis flowers include hypoglycemic, anti-cancer, antioxidant, hypolipidemic, modulation of gut health, antimicrobial activities, and anti-inflammatory activities. Other pharmacological properties are hepatoprotective, immunoregulatory, β-amyloid aggregation inhibitory, gastroprotective, nephroprotective, anti-obesity, anti-allergic, anti-cholesterol, pancreatic lipase inhibitory, melanin synthesis inhibitory, and non-alcoholic fatty liver disease activities. The potentials and challenges of the development of health supplements and other commercial products from tea flowers are discussed.
Keywords: Tea flowers, catechins, polysaccharides, saponins, anti-cancer, hypoglycemic